Electronic instrument design - Kim R. Fowler (Oxford University Press, 2006)
Electronic Instrument Design provides a coherent and integrated presentation of the design process, connecting engineering principles to real applications from a systems perspective. Bridging theory and practice, this hands-on guide builds a framework for developing electronic instrumentation, from hand-held devices to consoles of equipment. It offers practical design solutions, describes the interactions, trade-offs, and priorities encountered, and uses specific details, situations, and numerous case studies as examples. The methods may be applied to single prototypes as well as to mass-produced devices. The applications are not technology-dependent, and will therefore not be outdated by the next generation of hardware or software. While the focus of the book is on projects often found in small- or medium-sized companies, many of the principles presented apply to larger projects as well. Electronic Instrument Design is an ideal text for design courses in electrical and industrial engineering, and also serves as a practical guide for engineers in diverse fields